Pengembangan dan Validasi Instrumen Kepercayaan Diri Siswa dalam Merespon - Rizky Andana Pohan (Universitas PGRI Palembang, 2023)
The activity of responding to learning in the classroom is one of the indicators of the success of the learning process. One aspect that is very influential on students' ability to respond during learning is self-confidence. This study aims to develop and validate a student confidence instrument in responding to learning that can be used by counselors / counseling teachers in schools and researchers in the field of counseling. The instrument developed can measure students' level of confidence in responding. This research and development study was conducted in 2015 at SMA Negeri 8 Padang. The aspects of self-confidence measured in the instrument include: believing in themselves in responding, thinking positively in responding, having an internal locus of control in responding, and daring to accept and face the rejection of others in responding based on the theory of Fatimah (2008); Lauster (2012); Goel and Agarwal (2012). The validity test uses product moment correlation with an overall item validity value of 0.441. The reliability test used the Croncbach Alpha formula with a coefficient value of 0.705. The results of this data analysis mean that the self-confidence instrument in responding can be declared valid and reliable. So that the instrument of student confidence in responding to the developed can be used by school counselors / counseling teachers and counseling researchers to be able to measure the level of student confidence in responding to learning in the classroom.